Is multiple SNP testing in BRCA2 and BRCA1 female carriers ready for use in clinical practice? Results from a large Genetic Centre in the UK. (20th November 2012) - Ingham, SL; Warwick, J; Byers, H; Lalloo, F; Newman, WG; Evans, DGR
<x xml:space="preserve">Abstract</x> BRCA1 and BRCA2 are major breast cancer susceptibility genes. Nineteen single nucleotide polymorphisms (SNPs) at 18 loci have been associated with breast cancer. We aimed to determine whether these predict breast cancer incidence in women with BRCA1/BRCA2 mutations. BRCA1/2 mutation carriers identified through the Manchester genetics centre between 1996 and 2011 were included. Using published odds ratios (OR) and risk allele frequencies, we calculated an overall breast cancer risk SNP score (OBRS) for each woman. The relationship between OBRS and age at breast cancer onset was investigated using the Cox proportional hazards model, and predictive ability assessed using Harrell's C concordance statistic. In BRCA1 mutation carriers we found no association between OBRS and age at breast cancer onset: OR for the lowest risk quintile compared to the highest was 1.20 (95% CI 0.82–1.75, Harrell's C = 0.54), but in BRCA2 mutation carriers the association was significant (OR for the lowest risk quintile relative to the highest was 0.47 (95% CI 0.33–0.69, Harrell's C = 0.59). The 18 validated breast cancer SNPs differentiate breast cancer risks between women with BRCA2 mutations, but not BRCA1. It may now be appropriate to use these SNPs to help women with BRCA2 mutations make maximally informed decisions about management options.